2023
DOI: 10.1039/d2tb02345h
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional and multimodality theranostic nanomedicine for enhanced phototherapy

Abstract: Photodynamic therapy (PDT) has attracted much attention in recent years for their favorable efficacy in cancer therapy. However, monotherapy triggered by PDT alone are insufficient to improve therapeutic efficiency mainly...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…However, their limited sensitivity to soft tissues is a major obstacle to their clinical use. Fortunately, the advent of MRI has addressed this issue by offering lower resolution but greater sensitivity to soft tissues through nonionizing radiation. Since Mn 2+ possesses 5 unpaired electrons, it has been used as an ideal T1 contrast agent because the T1 contrast effect is generally manifested by the interaction between the electron spins of the contrast agent and the protons of water molecules. Thus, the presence of abundant PAA-Mn on the opposite side of JNPs has the potential to serve as a T1-weighted MR contrast.…”
Section: Discussionmentioning
confidence: 99%
“…However, their limited sensitivity to soft tissues is a major obstacle to their clinical use. Fortunately, the advent of MRI has addressed this issue by offering lower resolution but greater sensitivity to soft tissues through nonionizing radiation. Since Mn 2+ possesses 5 unpaired electrons, it has been used as an ideal T1 contrast agent because the T1 contrast effect is generally manifested by the interaction between the electron spins of the contrast agent and the protons of water molecules. Thus, the presence of abundant PAA-Mn on the opposite side of JNPs has the potential to serve as a T1-weighted MR contrast.…”
Section: Discussionmentioning
confidence: 99%
“…Both the in vitro and in vivo experiments showed that HMnO 2 /C&P exhibited excellent antitumor effects through combined PDT and mPTT. [ 117 ] In another research, Zhang group reported a photothermal bacterium (PTB) that utilized facultative anaerobic bacterium Shewanella oneidensis MR‐1 ( S. oneidensis MR‐1) and palladium nanoparticles (PD‐NPS) for PTT (Figure 3B). PTB exhibited strong photothermal properties and tumor‐targeting ability.…”
Section: Nanomedicine Mediated Mpttmentioning
confidence: 99%
“…Reproduced with permission. [ 117 ] Copyright 2023, Journal of Materials Chemistry B. B) Schematic of PTB@ZIF‐90/MB for PDT and mPTT.…”
Section: Nanomedicine Mediated Mpttmentioning
confidence: 99%
“…Undoubtedly, these unique characteristics are particularly beneficial for anticancer applications, such as photodynamic therapy and magnetic resonance imaging. , MnO 2 can be easily decomposed into Mn 2+ , which has a strong magnetic resonance imaging signal. , As we all know, some anticancer drugs not only exhibit significant damage to normal cells but also have a reduced killing effect on tumor cells due to the influence of the tumor microenvironment . For instance, the complex tumor microenvironments can inhibit the anticancer effects of some chemotherapy drugs, such as doxorubicin and cisplatin (CDDP), which bind to GSH and H 2 O 2 , etc. Fortunately, more and more studies have shown that nanostructured MnO 2 is of great significance in the delivery of anticancer drugs and enhancing the effectiveness of chemotherapy. Generally, the MnO 2 nanocarriers for anticancer drug delivery usually exhibit satisfactory tumor microenvironment-responsive drug release properties, and the degraded Mn 2+ has important applications in magnetic resonance imaging. , …”
Section: Introductionmentioning
confidence: 99%
“…21,22 MnO 2 can be easily decomposed into Mn 2+ , which has a strong magnetic resonance imaging signal. 23,24 As we all know, some anticancer drugs not only exhibit significant damage to normal cells but also have a reduced killing effect on tumor cells due to the influence of the tumor microenvironment. 25 For instance, the complex tumor microenvironments can inhibit the anticancer effects of some chemotherapy drugs, such as doxorubicin and cisplatin (CDDP), which bind to GSH and H 2 O 2 , etc.…”
Section: Introductionmentioning
confidence: 99%